Implementation of dose calculation methods for NORM by-products in building materials in the circular economy framework - La Verde, Giuseppe; Gagliardo, Gaetano; Ambrosino, Fabrizio; Pugliese, Mariagabriella (Frontiers in Built Environment, 2024)
Risk assessment of exposure to indoor pollutants plays an increasingly important role in human protection and one of the main sources is building materials. On the other hand, production processes, including those relating to building material, are also involved in the energy transition by evaluating the use of by-products from other industrial sectors as raw materials for their production process in compliance with environmental sustainability. In this work, we evaluate not only the radiation protection of building materials but also the possibility of adopting the circular economy principles. The two main objectives were: 1) radiometric characterization and calculation of Index I of pozzolan from Altavilla Irpina (Avellino) in Italy, used as a natural igneous additive for concrete, performed by gamma spectroscopy; 2) comparison between different methodologies for calculating the annual effective dose of building materials (CEN/TR 17113:2017, the RESRAD-BUILD software and a previously developed experimental method). The same approach was extended to the possibility of reusing fly asha NORM by-product of coal combustion in thermal power plantsfor the production of concrete. The study aligns with the principles linked to the circular economy as an extension of the life cycle of materials by reducing the need for natural resources, suggesting a possible positive compromise between radioprotection and preservation of environmental heritage.